PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SHAMPOO PANTENE DI KOTA METRO - Habiburrahman; Marsella Silvia (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The intensifying competition within the beauty and personal care industry in Indonesia coincides with the government's initiative to develop the cosmetics industry through the National Industrial Development Master Plan (RIPIN). Amongst the notable cosmetics brands, Pantene has established its prominence through iconic brand ambassadorship and good brand image. This research aims to investigate the impact of independent variables (brand ambassadors and brand image) on the dependent variable, namely purchasing decisions for Pantene shampoo. Employing a quantitative approach, the study undertakes descriptive data analysis and multiple linear regression. The research population consists of Pantene shampoo consumers within Metro City, with purposive sampling determining the sample. The findings from the partial significant test (t test) indicate that X1 (brand ambassador) and X2 (brand image) have a partially significant effect on Y (purchasing decision) of Pantene shampoo in Metro City. Moreover, the results from the simultaneous significant test (F test) demonstrate that X1 (brand ambassador) and X2 (brand image) have a significant influence simultaneously on the purchase decision of Pantene shampoo in Metro City.